2021
DOI: 10.3389/fevo.2021.698707
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Grazing Altered the Biodiversity–Productivity Relationship of Alpine Grasslands in Lhasa River Valley, Tibet

Abstract: Grazing is a crucial anthropogenic disturbance on grasslands. However, it is unknown how livestock grazing affects the relationship between biodiversity and productivity of alpine grasslands in Tibet. We carried out a grazing-manipulated experiment from 2016 to 2019 with grazing intensity levels of null (control, grazing exclusion, C.K.), moderate grazing [1.65 standardized sheep unit (SSU) per hectare, M.G.], and heavy grazing (2.47 SSU per hectare, H.G.) on a typical alpine grassland in the Lhasa River Basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 98 publications
(120 reference statements)
1
15
0
1
Order By: Relevance
“…Our results support the hypothesis that species turnover decreases with altitude only at the higher altitudinal zone. The lower species turnover in highlands could be attributed to the presence of sparse vegetation in mountainous areas generally [ 79 ], and probably, species turnover correlates with different rangeland management [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results support the hypothesis that species turnover decreases with altitude only at the higher altitudinal zone. The lower species turnover in highlands could be attributed to the presence of sparse vegetation in mountainous areas generally [ 79 ], and probably, species turnover correlates with different rangeland management [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…The availability of soil resources supports vegetation growth (Xu, Zhang, et al, 2019), changes plant community productivity (Xiang et al, 2021) and influences the composition of plant communities (García-Palacios et al, 2013). In our study, both G3 (heavy grazing) and G4 (overgrazing) significantly reduced soil OC and total N concentrations, and their low stocks, in turn, contributed negatively to plant productivity in the typical steppe.…”
Section: Grazing Intensity Effect On Plant Functional Types and Soil ...mentioning
confidence: 53%
“…Addington et al [35] reported that the stomatal apparatus controls Ψ in a way that the tension on the water column created by decreasing Ψ did not cause extreme xylem cavitation. Several studies suggested that high VPD reduces g s , consequently affecting assimilation rate and growth [84,85]. On the contrary, it has been argued that the impact of high VPD on g s may not possess any impact on assimilation rate and growth [86].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the impact of VPD on g s and/or assimilation rate varies amongst plant species [82]. In addition, the stomatal anatomy and structure affect water loss and carbon assimilation, demonstrating the evolution and adaptations of the plants to environmental conditions [84,87].…”
Section: Discussionmentioning
confidence: 99%